Lanthanide–organic frameworks constructed from naphthalenedisulfonates: structure, luminescence and luminescence sensing properties. Issue 31 (8th July 2016) - Li, Rui; Qu, Xiang-Long; Zhang, Yi-Hua; Han, Hong-Liang; Li, Xia
Abstract : Two series of Ln 3+ -coordination frameworks were synthesized. Highly luminescent pillared-layer Eu 3+ -framework1 is a promising luminescence sensor. Abstract : Two series of Ln 3+ -coordination frameworks were synthesized by using positional isomers of naphthalenedisulfonate (Nds) ligands, along with oxalate (ox) and 1, 10-phenanthroline (phen) ligands under the same experimental conditions, namely, {[Ln(1, 5-Nds)0.5 (ox)(phen)(H2 O)]·H2 O} n (Ln = Eu (1 ), La (2 ), and Sm (3 )), [La(2, 6-Nds)(ox)0.5 (phen)2 (H2 O)] n (4) and [Ln(2, 6-Nds)0.5 (ox)(phen)(H2 O)] n (Ln = Eu (5 ), Gd (6 ), and Tb (7 )). Compounds4 and5–7 show different grid-like layers with a {6 3 } topology based on [LaO5 N4 ] and [LnO6 N2 ] polyhedra as uninodal nodes, respectively. However, the 1, 5-Nds-based linker can pillar into a high dimensionality pillared-layer microporous motif of complexes1–3 with a {3 6 ·4 8 ·5 6 ·6} topology based on LnO7 N2 polyhedra as uninodal nodes, affording one-dimensional channels. Notably, highly luminescent microporous pillared-layer Eu 3+ -framework1 is a promising luminescence sensor for small organic molecules and metal ions, especially for benzaldehyde and Fe 3+ . The luminescence behavior of1 is affected by the solvents and the luminescence color changes from red-pink to blue. The possible luminescence sensing mechanism for Fe 3+ and the effect of using different solvents on the luminescence sensing of metal ions were explored. It is noteworthy that complex1 can be excited with a longer excitation wavelength (358 nm), which is an important requirement for applications.